The fat cat sat on the mat - Karlin, Nurit ([New York] : HarperCollins, 1996)
Rat tries to get the fat cat off the mat and back to his usual resting place in the vat.
Keywords: Cats -- Fiction; Rats -- Fiction; Witches -- Fiction; Brooms and brushes -- Fiction; Stories in rhyme